Meta-Analysis of Correlations between Work Stress and Burnout with Work Satisfaction in Nurses - Arista Gunawati; Agus Kristiyanto; Hanung Prasetya (Journal of Epidemiology and Public Health, 2022)
Background: Nurses are one of the human resources in the field of health services. Human resources who work in the service sector mostly have high levels of stress and burnout. The level of stress and burnout affect the work satisfaction of nurses. This study aims to determine the relationship between work stress and burnout with nurses’ work satisfaction.Subjects and Method: This study is a systematic review and meta-analysis by searching for articles published by the online database including PubMed, ResearchGate, Science Direct, Google Schoolar and EBSCO in 2007 to 2022. PICO variable work stress (Population: nurses, Intervention: heavy stress, Comparison: heavy stress, Outcome: work satisfaction). PICO variable burnout (Population: nurses, Intervention: heavy burnout, Comparison: heavy burnout, Outcome: work satisfaction). Data analysis was using RevMan software version 5.3.Results: Nurses who experience heavy or severe stress have a risk of lowering work satisfaction by 0.97 times compared to mild work stress, but it is not statistically significant (aOR= 0.97; 95% CI 0.78 to 1.20; p=0.750). Nurses who experience heavy burnout have a risk of reducing job satisfaction 0.87 times compared to mild job burnout, but it is not statistically significant (aOR= 0.87; CI 95% 0.58 to 1.30; p= 0.490).Conclusion: High stress levels can reduce nurses’ work satisfaction. A high level of burnout can reduce nurses’ work satisfaction. Keywords: burnout, nurse, work satisfaction, work stress. Correspondence:Arista Gunawati. Masters Program in Public Health Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: aristagunawati@gmail.com. Mobile: +6285647093646.